RISK COMMUNICATION IN CIGARETTE HEALTH WARNING LABELS AND BEHAVIOR CHANGE IN KENYA: A QUALITATIVE STUDY - Khaoya, Maureen; Mogambi, Hezron (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2024)
Background: The introduction of three-picture health warnings on cigarette packs, approved in 2014 and implemented in 2018, aimed to raise awareness and educate the public about the dangers of smoking. Therefore, the effectiveness of health warning labels on tobacco products is being questioned due to consumer reluctance to pay attention to the visuals or textual content. Purpose: This paper examines risk communication messages on cigarette warning labels that promote behavior change among adult smokers. Methods: The study focused on adults aged between 30 and 40 years who were smokers. Participants were selected from smoking zones in Kitui and Machakos Counties, Kenya. Data were collected through focus group discussions (FGDs). Results: According to FGDs, cigarette warning labels were found to influence how Kenyan adult smokers perceive health risks. The labels were observed to enhance understanding of tobacco-related risks among smokers and evidence of optimism bias among the smokers, indicating that they may be overly optimistic about their own health risks compared to others. While the labels were associated with a reduction in smoking habits, it was noted that this effect had limitations. The warning labels were deemed crucial but insufficient to induce a significant change in behavior. Conclusion: It was concluded that current cigarette warning labels in Kenya have a limited influence on risk perception among adult smokers. Importance of targeted communication strategies addressing optimism bias, to effectively combat risk perception among adult smokers is needed. Also, relatable and clear imagery could help smokers better understand and internalize potential health consequences.